2015
DOI: 10.3390/app5041076
|View full text |Cite
|
Sign up to set email alerts
|

The Preparation and Application of Dendrimer Modified CdTe/CdS Near Infrared Quantum Dots for Brain Cancer Cells Imaging

Abstract: Abstract:The most notable obstacle of brain cancer diagnosis is the inability of delivering imaging agents across the blood-brain barrier (BBB). Recently, quantum dots (QDs) has been demonstrated as an ideal image agent for brain imaging due to their ultra-small size for crossing BBB. The plolyamidoamine dendrimers modified CdTe/CdS core/shell near-infrared (NIR) region QDs was successfully synthesized in aqueous solution, and then was characterized by UV-vis absorption, photoluminescence (PL) spectroscopy, dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…This modification also extended the photoluminescence lifetime of QDs. Furthermore, the photoluminescence intensity of dendrimer-modified QDs decreased in acidic conditions due to the surface charge characteristics of dendrimer-modified QDs [ 196 ].…”
Section: Inps As Cores Of Dendrimersmentioning
confidence: 99%
“…This modification also extended the photoluminescence lifetime of QDs. Furthermore, the photoluminescence intensity of dendrimer-modified QDs decreased in acidic conditions due to the surface charge characteristics of dendrimer-modified QDs [ 196 ].…”
Section: Inps As Cores Of Dendrimersmentioning
confidence: 99%
“…Currently, QDs are still under investigation for their potential cytotoxic profiles. To minimize toxicity, QDs can be incorporated into nontoxic carriers such as dendrimers and liposomes [170, 171]. Despite their potential hazardous side effects, QDs hold a great promise for the future of brain cancer treatment.…”
Section: Application Of Nanotechnology For Brain Cancer Imagingmentioning
confidence: 99%
“…However, the microscopic size (usually <10 nm) of quantum dots can overcome this challenge, making it an ideal agent for imaging of brain tumours. [54][55][56][57] Bai et al 55 demonstrated that quantum dots have promising potential for in vivo brain imaging due to the small size and narrow emission spectra. Quantum dots have also been combined with nanoparticles to enhance image-guided brain tumour excision procedures.…”
mentioning
confidence: 99%